PENGEMBANGAN MASJID LUAR BATANG SEBAGAI BAGIAN DARI POTENSI WISATA KAWASAN PELABUHAN SUNDA KELAPA - Wisnu Ivan Kusuma; Lin Yola (LPPM Institut Pendidikan Nusantara Global, 2023)
An Nur Mosque or better known as the Luar Batang Mosque in the coastal area in North Jakarta is a historical heritage built in 1739. Until now, the Luar Batang Mosque, which is considered sacred, has been visited by many people both from Jakarta and outside Jakarta. As a religious tourism location, the Luar Batang Mosque currently has many limitations both physical and non-physical facilities, such as the lack of parking lots, limited visitor accommodation and the lack of availability of information that can be obtained by the public if they want to visit. The research conducted through this qualitative method was carried out to provide recommendations to the management of the Luar Batang Mosque and the DKI Jakarta Provincial Government to be able to develop the potential of religious tourism to make it more friendly and comfortable for visitors and provide benefits to the surrounding community, as is done at the Jogokariyan Mosque in Yogyakarta or the historic Kebon Jeruk Mosque in West Jakarta.